Depreciation to correct trade deficit- a misdirected policy: Empirical evidence from Pakistan - Hina, Hafsa; Hye, Qazi Muhammad Adnan; Ul-Haq, Jabbar (Asian Journal of Economic Modelling, 2023)
A favorable trade balance is a positive indicator for emerging economies, and rectifying trade imbalances is paramount for every country. However, fixing trade deficits by depreciating the currency is a misguided policy approach. This study refutes this myth by computing the elasticity of Pakistan’s exports, imports, and trade balance using the real exchange rate. It also examines the degree to which trade elasticities respond to changing trade regimes and exchange rate policies in Pakistan from 1982 to 2019. The structural break cointegration technique is used for empirical analysis. The vector error correction model (VECM) is also employed in the study to establish long-run and short-run relationships. The findings show that depreciation boosts import demand rather than export demand, hence worsening the trade balance. As a result, the study dismisses the presence of the J-curve in the case of Pakistan. According to this analysis, the exchange rate policy has little bearing on the economy’s structure, and the necessity for a devaluation results from economic structural inefficiencies rather than trade-enhancing policies. The government and policymakers should reform the economy rather than let the currency depreciate.